Association of CD14 with incident dementia and markers of brain aging and injury. (21st January 2020) - Pase, Matthew P.; Himali, Jayandra J.; Beiser, Alexa S.; DeCarli, Charles; McGrath, Emer R.; Satizabal, Claudia L.; Aparicio, Hugo J.; Adams, Hieab H.H.; Reiner, Alexander P.; Longstreth, W.T.; Fornage, Myriam; Tracy, Russell P.; et al.
Abstract : Objective: To test the hypothesis that the inflammatory marker plasma soluble CD14 (sCD14) associates with incident dementia and related endophenotypes in 2 community-based cohorts. Methods: Our samples included the prospective community-based Framingham Heart Study (FHS) and Cardiovascular Health Study (CHS) cohorts. Plasma sCD14 was measured at baseline and related to the incidence of dementia, domains of cognitive function, and MRI-defined brain volumes. Follow-up for dementia occurred over a mean of 10 years (SD 4) in the FHS and a mean of 6 years (SD 3) in the CHS. Results: We studied 1, 588 participants from the FHS (mean age 69 ± 6 years, 47% male, 131 incident events) and 3, 129 participants from the CHS (mean age 72 ± 5 years, 41% male, 724 incident events) for the risk of incident dementia. Meta-analysis across the 2 cohorts showed that each SD unit increase in sCD14 was associated with a 12% increase in the risk of incident dementia (95% confidence interval 1.03–1.23; p = 0.01) following adjustments for age, sex, APOE ε4 status, and vascular risk factors. Higher levels of sCD14 were associated with various cognitive and MRI markers of accelerated brain aging in both cohorts and with a greater progression of brain atrophy and a decline in executive function in the FHS. Conclusion: sCD14 is an inflammatory marker related to brain atrophy, cognitive decline, and incident dementia.